High and low temperature resistant conductive antibacterial hydrogel as well as preparation method and application thereof
By using hydrogen bonds in conductive hydrogels to stabilize moisture and induce cross-linking of silver nanoparticles, the problem of the loss of flexibility at low temperatures and loss of conductivity at high temperatures is solved, and a conductive antibacterial hydrogel that is resistant to high and low temperatures is prepared. The stable performance and antibacterial effect under extreme conditions were achieved.
Patent Information
- Application Number
- CN202411525155.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing conductive hydrogels freeze at low temperatures and lose flexibility. When the water evaporates at high temperatures, they lose conductivity. In addition, there are hidden health risks such as microbial pollution in biological signals, which cannot meet the flexible transmission of large deformation scenarios such as human movement. Feeling demand.
By using polymer alcohol polymers in the mixed solution in low freezing point to form hydrogen bonds with water molecules, stabilize moisture, and induce physical crosslinking of silver nanoparticles in the freezing-thawing treatment, conducting antibacterial hydrocoagulation that is resistant to high and low temperatures is prepared. Glue ensures that mechanical properties and electrical conductivity are maintained within the range of -30℃ to 70℃.
It achieves good mechanical properties and conductivity at extreme temperatures, has antibacterial effects, is suitable for applications such as flexible sensing and biological signal acquisition, and meets the needs under extreme conditions.
Smart Images

Figure CN119264470A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multifunctional flexible conductive polymer materials, and in particular to a high and low temperature resistant conductive antibacterial hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogel is a kind of network structure polymer with hydrophilic groups, which can be swollen but insoluble in water. It is composed of 3D polymer network and a large amount of water. It has the characteristics of "soft" and "wet". It has many similarities with the soft tissues (organs, muscles, skin) of organisms in structure and composition. It has the advantages of environmental friendliness, biocompatibility, anti-biological pollution and perception of external stimuli. It is widely used in cell culture, biological tissue engineering, biosensor, drug controlled release, soft robots, flexible wearables and other fields. At present, in order to meet the needs of more complex application scenarios, a large number of hydrogel functional modification studies have been carried out, such as mechanically enhanced hydrogels, environmentally responsive hydrogels (temperature response, pH response, light, force, ion solubility, redox, magnetic field, electric field, ultrasound, etc.), conductive hydrogels, self-healing hydrogels, self-adhesive hydrogels, antibacterial hydrogels, etc. In addition, the interdisciplinary and cross-field cooperation in the research and development of multifunctional hydrogels (MFHs) with integrated intelligent environmental response, complex driven deformation, patterning and other functions has become an obvious development trend.
[0003] Among them, conductive hydrogels have biocompatibility, flexible three-dimensional mesh structure, conductivity and some unique functionality. They have attracted widespread attention in the fields of flexible sensing and bioelectronics, and are considered to be one of the ideal interface materials for achieving perfect compatibility between human body and bioelectronics in biosimulation, artificial neural network, etc., which has attracted widespread attention in the industry. Conductive hydrogels have broad application prospects in flexible wearable electronic products, energy storage, energy conversion and electrochemical biosensors. Conductive hydrogels with conductive, soft, transparent and biocompatible characteristics have natural advantages in combination with flexible electronics.
[0004] At present, most hydrogels are ion conductive. The research on conductive hydrogels is relatively scattered and has not yet formed a systematic study. The main problems in practical applications are: (1) Poor mechanical properties, especially insufficient tensile properties, which cannot meet the flexible sensing and smart wearable sensing requirements of large deformation scenarios such as human movement; (2) In sub-zero low-temperature environments, water freezes, and the hydrogel material becomes hard, brittle, and loses flexibility; when exposed to air or above room temperature, the water evaporates, the hydrogel material loses water and shrinks, collapses and shrivels; (3) Hydrogel materials based on ion conductivity will lose conductivity due to the lack of freely movable ions when the low-temperature water freezes or the high-temperature water evaporates and is lost; (4) When used for biological signal acquisition, especially in body-attached testing scenarios, there are health risks such as microbial contamination. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a high and low temperature resistant conductive antibacterial hydrogel and its preparation method and application. The preparation method is simple and the conditions are mild. The prepared conductive antibacterial hydrogel can maintain good mechanical properties, conductivity and stability in the temperature range of -30°C to 70°C, and has antibacterial and antibacterial effects. It can be used for flexible sensing and biological signal acquisition under extreme conditions.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a high and low temperature resistant conductive antibacterial hydrogel, comprising the following steps:
[0008] (1) dissolving a high molecular alcohol polymer in a low freezing point mixed solution to obtain a pre-gel solution;
[0009] (2) adding a silver salt solution to the pre-gel solution obtained in step (1) at 85° C. to 95° C. to react to obtain a hydrogel precursor solution;
[0010] (3) The hydrogel precursor solution obtained in step (2) is subjected to freeze-thaw treatment to obtain the high and low temperature resistant conductive antibacterial hydrogel.
[0011] The present invention utilizes a large number of hydrogen bonding forces between the effective components and water molecules in the low-freezing point mixed solution to stabilize the water, so that it does not freeze at low temperatures and does not evaporate at high temperatures within a wide temperature range of -30°C to 70°C; utilizes the reducing properties of high-molecular alcohol polymers and polyols in the low-freezing point mixed solution to reduce the silver salt solution to silver nanoparticles (AgNPs), and the high-molecular alcohol polymer also acts as a dispersant and stabilizer to prevent the silver nanoparticles from agglomerating, achieving antibacterial and conductive properties; during the freezing process, the high-molecular alcohol polymer polymer chain forms a large number of hydrogen bonds with the low-freezing point mixed solution, and induces the high-molecular alcohol polymer to form a crystalline region, as well as the physical cross-linking points of the silver nanoparticles, and these physical cross-links give the hydrogel good mechanical properties and adjustability. The preparation process provided by the present invention is simple and mild, and can be applied to flexible sensing, biological signal acquisition, optical sensing and imaging under extreme conditions.
[0012] Furthermore, in step (1), the high molecular alcohol polymer is selected from one or more of polyvinyl alcohol (PVA), polyethylene glycol (PEG), polypropylene glycol (PPG) and polybutylene glycol (PBD).
[0013] Furthermore, in step (1), the average molecular weight of the high molecular alcohol polymer is 20,000-150,000.
[0014] Furthermore, in step (1), the alcoholysis degree of the high molecular alcohol polymer is 87%-89% (mol / mol).
[0015] Furthermore, in step (1), the high molecular alcohol polymer is preferably polyvinyl alcohol, and the polyvinyl alcohol is preferably type 1788. Furthermore, in step (1), the low freezing point mixed solution is a mixed solution of one or more polyols and water.
[0016] Furthermore, the polyol is ethylene glycol, glycerol, propylene glycol, butylene glycol, etc.
[0017] Furthermore, in step (1), in the low freezing point mixed solution, the mass ratio of water to polyol is 1:9-9:1.
[0018] Furthermore, in step (1), the low freezing point mixed solution is preferably a mixed solution of glycerol and water.
[0019] In a binary mixed solution of water and glycerol, hydrogen bonds are formed between water molecules and the hydroxyl groups in glycerol. Both PVA and glycerol are rich in hydroxyl groups, and a large number of hydrogen bonds are also present in the prepared hydrogel. A large number of hydrogen bonds can firmly lock the water molecules, giving them a low freezing point and evaporation rate, and thus having good frost resistance and moisture retention. The freezing point of a binary mixed solution of water and glycerol can be adjusted by the mixing ratio of the two.
[0020] Furthermore, in step (1), the mass ratio of the low freezing point mixed solution to the high molecular alcohol polymer is 100:(5-20).
[0021] Furthermore, in step (1), the high molecular alcohol polymer is dissolved in the low freezing point mixed solution at 50°C to 95°C.
[0022] In a specific embodiment, in step (1), the high molecular alcohol polymer is uniformly dissolved in the low freezing point mixed solution under heating and stirring conditions to obtain a pre-gel solution.
[0023] Furthermore, the heating temperature is preferably 80°C to 90°C.
[0024] Furthermore, the stirring speed is 70-80 rpm and the time is 4-5 h.
[0025] Furthermore, in step (2), the silver salt solution is a silver salt aqueous solution.
[0026] Furthermore, in step (2), the silver salt solution is selected from one or more of a silver ammonia solution, a silver nitrate solution, a silver oxalate solution, a silver chloride solution and a silver bromide solution, preferably a silver ammonia solution.
[0027] Furthermore, in step (2), the mass ratio of the pre-gel solution to the silver ions in the silver salt solution is (30-70):(0.2-1.5), preferably (30-70):(0.3-1.3), and more preferably (30-70):(0.6-1.3).
[0028] Furthermore, in step (2), the silver ammonia solution is prepared from silver nitrate, water and aqueous ammonia, and the mass ratio of the pre-gel solution to silver nitrate is (30-70):(0.5-2), preferably (40-60):(1-2).
[0029] In a specific embodiment, in step (2), a silver salt solution is added to the pre-gel solution obtained in step (1) at 85° C. to 95° C. under stirring conditions, and the reaction is maintained for a period of time to ensure that all silver ions are reduced to uniformly dispersed elemental silver particles to obtain a hydrogel precursor solution.
[0030] Furthermore, the stirring speed is 70-80 rpm and the time is 2-3 h.
[0031] Furthermore, in step (3), the freeze-thaw treatment conditions are: freezing at -25°C to -20°C, and thawing at 0°C to 70°C.
[0032] In a specific embodiment, in step (3), the hydrogel precursor solution is left to stand overnight for degassing and defoaming, poured into a mold, and subjected to freeze-thaw treatment to obtain the high and low temperature resistant conductive antibacterial hydrogel.
[0033] Furthermore, the mold is a national standard mechanical property test mold or other mold of required shape.
[0034] The second aspect of the present invention provides a high and low temperature resistant conductive antibacterial hydrogel prepared by the method described in the first aspect.
[0035] The high and low temperature resistant conductive antibacterial hydrogel provided by the present invention maintains good mechanical properties, conductivity and stability within the temperature range of -30°C to 70°C, has an elongation at break of up to 440%, a tensile strength of up to 0.75Mpa, good compression resilience, can recover quickly under 60% compression strain, and has good inhibitory and killing effects on Escherichia coli and Staphylococcus aureus.
[0036] The third aspect of the present invention provides the application of the high and low temperature resistant conductive antibacterial hydrogel described in the second aspect in sensors and biological signal acquisition, which can be applied to flexible sensing, optical sensing and imaging under extreme conditions, such as flexible strain sensors, flexible temperature sensors, etc.
[0037] Beneficial effects of the present invention:
[0038] 1. The present invention utilizes a large amount of hydrogen bonding forces formed between the effective ingredients and water molecules in the low-freezing point mixed solution to stabilize the water, so that the low-temperature water does not freeze and the high-temperature water does not evaporate within a wide temperature range of -30°C to 70°C, and maintains good mechanical properties and morphology.
[0039] 2. The present invention utilizes the reducing property of a low freezing point mixed solution and polyols (such as ethylene glycol, propylene glycol, and high molecular alcohol polymers) to reduce the silver salt solution to produce silver nanoparticles. At the same time, the high molecular alcohol polymers also act as dispersants and stabilizers to prevent the silver particles from agglomerating and to distribute them evenly, thereby achieving antibacterial and conductive properties.
[0040] 3. In the process of cyclic freezing in the preparation method of the present invention, the polymer chains of the high molecular alcohol polymer form a large number of hydrogen bonds with the low freezing point mixed solution, and induce the high molecular alcohol polymer to form crystalline regions, as well as the physical crosslinking points of the silver nanoparticles. These physical crosslinks give the hydrogel good mechanical properties and adjustability.
[0041] 4. The preparation process provided by the present invention is simple and the conditions are mild, and it can be applied to flexible sensing, biological signal collection, optical sensing and imaging under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a physical diagram of the reaction of step (2) in Example 1.
[0043] Figure 2 Actual pictures of hydrogel samples with different shapes.
[0044] Figure 3 This is a physical picture of the freezing of ordinary PVA hydrogel in Comparative Example 1.
[0045] Figure 4 The test results of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 are shown in Figures 1 and 2; wherein (a) is a temperature and humidity change data graph in an indoor open environment, (b) is a weight change rate data graph of the hydrogel samples of Examples 1-3 and Comparative Example 1 in an indoor open environment, (c) is a comparison of the appearance of the hydrogel sample of Example 1 and the PVA hydrogel sample without glycerol, (d) is a weight change rate data graph of the hydrogel samples of Examples 1-3 and Comparative Example 1 under 70°C oven conditions, (e) is a weight change rate data graph of the hydrogel samples of Examples 1-3 and Comparative Example 1 under -30°C freezing conditions, and (f) is a physical picture showing the antifreeze performance of the hydrogel sample of Example 1.
[0046] Figure 5The figures are the test results of the mechanical properties of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1; wherein, (a) is a stress-strain curve diagram of the tensile test (the curves are Comparative Example 1, Example 1, Example 2, and Example 3 from bottom to top), (b) is a stress-strain curve diagram of the compression test (the curves are Comparative Example 1, Example 1, Example 2, and Example 3 from bottom to top), (c) is a data diagram of the elastic modulus, (d) is a physical diagram of the tensile and compression tests, (e) is a data table of the elastic modulus of different human tissues, (f) is a physical diagram of the hydrogel sample of Example 1 being cut and extremely compressed, and (g) is a physical diagram of the light transmittance test.
[0047] Figure 6 The (strain sensing) conductivity test result diagrams of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1; wherein, (a) is a data diagram of the resistance change and tensile strain sensitivity of the hydrogel sample of Comparative Example 1 within a 200% stretching range, (b) is a data diagram of the resistance change and tensile strain sensitivity of the hydrogel sample of Example 1 within a 200% stretching range, (c) is a data diagram of the resistance change and tensile strain sensitivity of the hydrogel sample of Example 2 within a 200% stretching range, (d) is a data diagram of the resistance change and tensile strain sensitivity of the hydrogel sample of Example 3 within a 200% stretching range, and (e) is a data diagram of the resistance change and tensile strain sensitivity of the hydrogel sample of Example 3 within a 200% stretching range. Figure 2 is a physical picture of the simultaneous collection of resistance signals during the extension and compression process, (f) is the resistance change and compression strain sensitivity of the hydrogel sample of comparative example 1 within a 60% compression range, (g) is the resistance change and compression strain sensitivity of the hydrogel sample of example 1 within a 60% compression range, (h) is the resistance change and compression strain sensitivity of the hydrogel sample of example 2 within a 60% compression range, (i) is the resistance change and compression strain sensitivity of the hydrogel sample of example 3 within a 60% compression range, (j) is a graph of the strain test results of the hydrogel sample of example 3 for different bending angles of the finger, and (k) is the response and recovery time of the hydrogel sample of example 1 for a hydrogel flexible strain sensor.
[0048] Figure 7The (temperature sensing) conductivity test result graphs of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1; wherein, (a) is a resistance change graph of the hydrogel samples of Examples 1-3 and Comparative Example 1 in the temperature range of -30°C to 70°C, (b) is a resistance change graph and its TCR graph of the hydrogel sample of Comparative Example 1 in the temperature range of -20°C to 25°C, (c) is a resistance change graph and its TCR graph of the hydrogel sample of Example 1 in the temperature range of -20°C to 25°C, (d) is a resistance change graph and its TCR graph of the hydrogel sample of Example 2 in the temperature range of -20°C to 25°C, and (e) is a resistance change graph and its TCR graph of the hydrogel sample of Example 3 in the temperature range of -20°C to 25°C.
[0049] Figure 8 The antibacterial performance test results of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 are shown; wherein (a) is a test result diagram of the inhibition zone method, and (b) is a test result diagram of the oscillation culture method. DETAILED DESCRIPTION
[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0052] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0053] Example 1
[0054] A method for preparing a high and low temperature resistant conductive antibacterial hydrogel (PVA-glycerol-Ag0.5 organohydrogel), comprising the following steps:
[0055] (1) At 85°C, 4 g of polyvinyl alcohol was dissolved in 10.4 mL of water and 28 mL of glycerol (GL) and stirred at 80 rpm for 4 h to obtain a pregel solution.
[0056] (2) Adding a silver ammonia solution to the pre-gel solution obtained in step (1) at 85° C., the silver ammonia solution being prepared from 0.5 g of AgNO 3 , 1 mL of H 2 O and 0.6 mL of aqueous ammonia, stirring at 80 rpm for 2 h, and reacting to obtain a hydrogel precursor solution.
[0057] (3) The hydrogel precursor solution obtained in step (2) is allowed to stand overnight to degas and remove bubbles, poured into a mold, and subjected to freeze-thaw treatment: freezing at -20°C for 5 hours, thawing at room temperature for 2 hours, and repeating the cycle twice to obtain the high and low temperature resistant conductive antibacterial hydrogel.
[0058] Figure 1 The reaction diagram of step (2) in Example 1 is shown in FIG. Figure 1 Ag can be seen in + The process of being restored.
[0059] Figure 2 The figures are actual pictures of hydrogel samples with different forms, which prove that the hydrogel prepared by the present invention can be prepared into different forms according to different molds.
[0060] Example 2
[0061] A method for preparing a high and low temperature resistant conductive antibacterial hydrogel (PVA-glycerol-Ag1.0 organohydrogel), comprising the following steps:
[0062] (1) At 85°C, 4 g of polyvinyl alcohol was dissolved in 9.8 mL of water and 28 mL of glycerol (GL) and stirred at 80 rpm for 4 h to obtain a pregel solution.
[0063] (2) Adding a silver ammonia solution to the pre-gel solution obtained in step (1) at 85° C., the silver ammonia solution being prepared from 1.0 g of AgNO 3 , 1 mL of H 2 O and 1.2 mL of aqueous ammonia, stirring at 80 rpm for 2 h, and reacting to obtain a hydrogel precursor solution.
[0064] (3) The hydrogel precursor solution obtained in step (2) is allowed to stand overnight to degas and remove bubbles, poured into a mold, and subjected to freeze-thaw treatment: freezing at -20°C for 5 hours, thawing at room temperature for 2 hours, and repeating the cycle twice to obtain the high and low temperature resistant conductive antibacterial hydrogel.
[0065] Example 3
[0066] A method for preparing a high and low temperature resistant conductive antibacterial hydrogel (PVA-glycerol-Ag2.0 organohydrogel), comprising the following steps:
[0067] (1) At 85°C, 4 g of polyvinyl alcohol was dissolved in 9.0 mL of water and 28 mL of glycerol (GL), and stirred at 80 rpm for 4 h to obtain a pregel solution.
[0068] (2) Adding a silver ammonia solution to the pre-gel solution obtained in step (1) at 85° C., the silver ammonia solution being prepared from 2.0 g of AgNO 3 , 1 mL of H 2 O and 2.0 mL of aqueous ammonia, stirring at 80 rpm for 2 h, and reacting to obtain a hydrogel precursor solution.
[0069] (3) The hydrogel precursor solution obtained in step (2) is allowed to stand overnight to degas and remove bubbles, poured into a mold, and subjected to freeze-thaw treatment: freezing at -20°C for 5 hours, thawing at room temperature for 2 hours, and repeating the cycle twice to obtain the high and low temperature resistant conductive antibacterial hydrogel.
[0070] Comparative Example 1
[0071] A method for preparing a PVA hydrogel (PVA-glycerol organohydrogel), comprising the following steps:
[0072] (1) At 85°C, 4 g of polyvinyl alcohol was dissolved in 12.0 mL of water and 28 mL of glycerol (GL), and stirred at 80 rpm for 4 h to obtain a pregel solution.
[0073] (2) The pre-gel solution obtained in step (1) was allowed to stand overnight to degas and remove bubbles, poured into a mold, and subjected to freeze-thaw treatment, freezing at -20°C for 5 hours and thawing at room temperature for 2 hours, and the cycle was repeated twice to obtain a hydrogel.
[0074] Figure 3 This is a physical picture of the freezing of ordinary PVA hydrogel without glycerol.
[0075] Test Example 1
[0076] The stability of the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 in high and low temperature environments was tested by the following test method:
[0077] The hydrogel samples were stored in an open environment indoors for 34 days, in a frozen state of -30°C for 30 days, and in an oven at 70°C for 16 hours. The state and weight change of the hydrogel samples were recorded to characterize the antifreeze performance and moisturizing ability of the hydrogel samples.
[0078] The weight change rate is calculated as follows:
[0079] Weight rate (%) = (W0-W t ) / W0*100%
[0080] Where W0 is the initial weight of the sample (g), W t is the weight after storage for a certain period of time (g).
[0081] Test results such as Figure 4 As shown, Figure 4 (a) records the changes in ambient temperature and humidity of the hydrogel sample stored in an open indoor environment for 34 days. Figure 4 As can be seen in (b), in an open indoor environment (20-34°C, 42-91% RH), the weight change rate of the sample is mainly affected by humidity. This is because PVA and propylene glycol have hydrophilic and hygroscopic properties, and the indoor temperature fluctuation is relatively small. The weight change rate of the four hydrogel samples is kept within 6.5%, which has good moisturizing properties. On the contrary, Figure 4 As can be seen in (c), the mass loss of the PVA hydrogel without glycerol is about 80%, and it becomes dry, brittle and hard due to the loss of water.
[0082] The hydrogel sample was placed in a 70°C oven for drying for 16 h, and the weight change rate of the hydrogel sample was recorded. The data is as follows: Figure 4 As shown in (d), the mass of the hydrogel sample basically no longer decreases after drying for 5 hours, and the mass loss rate decreases with the increase of AgNPs content. The maximum mass loss is about 5.5% and the minimum is only about 1.5%, highlighting its excellent moisturizing performance and stability.
[0083] The hydrogel samples were stored at -30°C for 30 days for antifreeze test, and the weight change rate of the hydrogel samples was recorded. The data are as follows: Figure 4 As shown in (e), the weight of the hydrogel sample increases slowly due to moisture absorption, and the weight increase rate decreases with the increase of AgNPs content. This is because the increase of physical cross-linking points of AgNPs makes the sample structure more compact, thereby reducing the amount of water absorbed. Moreover, after being frozen at -30°C for 30 days, the hydrogel sample of Example 1 can still maintain good flexibility and stretchability, and can bend under its own gravity. It is very soft and has no damage after being twisted more than 5 times and stretched more than 200%. Figure 4 As shown in (f).
[0084] The tests under the above three different conditions indicate that the hydrogel samples prepared by the present invention have excellent antifreeze, heat resistance and moisture retention properties, and can maintain good morphology and performance under extreme environments of -30°C and 70°C, meeting the application requirements of daily and special scenarios.
[0085] Test Example 2
[0086] The high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 were subjected to mechanical property tests. The stress-strain test method was as follows:
[0087] Select dumbbell-shaped samples for tensile testing at a tensile speed of 20 mm / min; select cylindrical samples for compression testing at a compression speed of 5 mm / min. The calculation method is as follows:
[0088]
[0089]
[0090] Where: σ is the tensile / compressive stress (MPa); F is the force borne during tension / compression (N);
[0091] A is the cross-sectional area of the sample (m 2 );δ is tensile / compressive strain (%);
[0092] L is the clamp distance during tension / compression (mm); L0 is the initial clamp distance (mm).
[0093] Generally speaking, the tensile strength and elongation at break of a material are negatively correlated, because the increase in material strength tends to reduce the tensile properties of the material. Figure 5 As shown in (a), the stress (tensile strength) and strain (elongation) of the tensile test of the hydrogel sample prepared by the present invention increase with the increase of the AgNPs content. This is because the AgNPs prepared by the reduction method are uniformly dispersed in the hydrogel matrix. On the one hand, as physical cross-linking points, they can enhance the tensile properties of the three-dimensional network of the gel; on the other hand, AgNPs, as a kind of nanoparticle, have the characteristics of small particle size and large specific surface area, which can effectively disperse stress and thus improve tensile strength. It can be seen from the stress-strain curve of the tensile test that AgNPs have a more obvious improvement on the tensile strength of the sample. The tensile strength at break is increased from about 2.82KPa to 0.751MPa, an increase of more than 260 times; the elongation at break is increased from 285% to 440%, an increase of 1.5 times. As shown in FIG. Figure 5 As shown in (f), the sample exhibits good toughness when cut and does not break even at the ultimate compression of 99% deformation (14.019 MPa), indicating good cross-linking strength.
[0094] According to Hooke's law, within the elastic limit of an object, stress and strain are proportional, and their ratio is the elasticity modulus (E), which can be calculated by Figure 5 The calculation is based on the slope of the initial linear region (tensile strain ε = 10-20%) of the stress-strain curve in (b). Figure 5As shown in (c), the tensile elastic modulus (E = σ / ε) of the four hydrogel samples are 0.99 KPa, 49.81 KPa, 74.38 KPa, and 170.76 KPa, respectively. The size of the elastic modulus reflects the hardness of the material. The larger the elastic modulus, the less likely the material is to deform. Materials with an elastic modulus of kilopascals or less are defined as "supersoft materials." By changing the content of AgNPs, the span from "supersoft materials" to general soft materials can be achieved, and its elastic modulus can match that of most biological tissues in the human body (such as Figure 5 The preparation method of the present invention does not contain harmful substances such as chemical crosslinking agents, and the crosslinking molding conditions are mild and the speed is suitable. Cells can be evenly mixed into the gel precursor solution, and the elastic modulus can be adjusted to induce different differentiation of cells. The prepared hydrogel can be used as an ideal scaffold material for 3D cell and tissue culture.
[0095] Most of the optical fibers currently used are silica fibers or high modulus polycarbonate fibers, which tend to cause damage to soft tissues. Therefore, the "super softness" and high light transmittance of the hydrogel prepared by the present invention are noteworthy. Figure 5 As shown in (c) and (g) in Figure 2, the laser can be injected into one end of a straight or curved hydrogel and emitted from the other end. Figure 5 After splicing 2 to 3 hydrogel segments together, it was found that the laser propagation was greatly hindered at the interface, as shown in (i) and (ii). Figure 5 Combined with the "super softness" of the hydrogel, the hydrogel prepared by the present invention can be used as a flexible optical fiber material in biomedical fields such as optical sensing and imaging.
[0096] Test Example 3
[0097] The high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 were tested for their conductive properties. The test method was as follows:
[0098] The resistance changes of different hydrogel samples were tested within a 200% stretching range, and the tensile strain sensitivity of the gel samples was evaluated by the sensitivity coefficient (GF), GF = [(R-R0) / R0] / ε, where R is the real-time resistance under tensile strain, R0 is the initial resistance when the strain is 0%, and ε is the tensile strain.
[0099] On the one hand, PVA is a polyelectrolyte rich in hydroxyl groups, which can dissociate in a water molecule environment and release a large number of protons (H + ), so PVA hydrogel has a certain ionic conductivity. Figure 6As shown in (a), the resistance of the hydrogel sample of Comparative Example 1 increases linearly with the tensile strain within a larger tensile strain range of 0% to 125%, GF = 3.5141 (R 2 =0.989); as the PVA polymer chain segments continued to break, the conductive network was destroyed, and the resistance increase trend fluctuated. However, the charge tunneling occurred between the uniformly distributed AgNPs in the hydrogel sample provided by the present invention to form a conductive network, so the addition of AgNPs significantly improved the conductivity. The resistance change of the sample containing AgNPs was mainly affected by the content and distribution of AgNPs. Figure 6 As shown in (b), (c) and (d), the resistance of the hydrogel sample increases with the increase of the average distance between AgNPs during stretching. In the range of 0% to 125% tensile strain, the resistance of the hydrogel sample of Example 1 fluctuates violently and has almost no linear region. The GF of the hydrogel sample of Example 2 is 2.1920 (R 2 =0.993), the GF of the hydrogel sample of Example 3 is 2.5072 (R 2 =0.969), and by comparison, it was found that the linear fit of the "tensile strain-resistance change" curve of the hydrogel sample of Example 2 was the best (R 2 =0.993), indicating that within a certain tensile strain range, the appropriate AgNPs content can improve the stability of the linear change of the sample resistance. When it is assembled into a flexible strain sensor, the high linearity is beneficial to the back-end acquisition circuit design and data processing. Compared with the hydrogel strain sensor reported in the relevant literature, the hydrogel prepared by the present invention has higher tensile strain sensitivity.
[0100] The resistance changes of different hydrogel samples were tested within a 60% compression range. The test results are shown in Figure 6 As shown in (f), (g), (h) and (i), the resistance of the hydrogel samples of Comparative Example 1 and Example 1 decreases linearly with the compression process, and their compression sensitivity coefficients (GF) are -1.370 (R 2 =0.990), -0.001(R 2 =0.996). The hydrogel samples of Example 2 and Example 3 exhibit negative pressure-sensitive properties during compression. As the compression strain increases, their GF values decrease, that is, they are more sensitive at low compression amounts. Their maximum compression sensitivity coefficients (GF) are -13.967 (0% to 5%, R 2 =0.983), -11.129 (0% ~ 7%, R 2=0.985). This is because as the content of AgNPs increases, the distance between the uniformly distributed AgNPs in the hydrogel sample becomes smaller, and compression shortens the distance of the hydrogel sample in the axial direction and makes the AgNPs more densely arranged, forming a good conductive path, and the resistance decreases rapidly; afterwards, due to the formation of the conductive path, the effect of compression on the resistance of the hydrogel sample is small, but within this range, the resistance still decreases linearly with compression, and the compression sensitivity coefficient (GF) of the hydrogel samples in Example 2 and Example 3 is reduced to -0.1369 (25% to 60%, R 2 =0.969), -0.0368 (25% ~ 60%, R 2 =0.992).
[0101] From the above test, it can be seen that the resistance of the hydrogel sample increases when stretched and decreases when compressed, and is linearly correlated within a certain strain range. In order to verify the application in the field of flexible wearables, the hydrogel sample of Example 3 with elastic modulus similar to that of human muscle and cartilage tissue was selected to make a gel strain sensor for monitoring the repetitive motion signals of fingers at different bending angles (30°, 60°, 90°). Figure 6 As shown in (j), when the finger is bent, the gel strain sensor is stretched, and its relative resistance changes rapidly increase. When the finger returns to its original position, its relative resistance changes rapidly decrease and recover, indicating that the gel strain sensor has high sensitivity. In the continuous repeatability test, its relative resistance change shows good stability and repeatability (the occasional small fluctuations are caused by the deviation of the volunteer's finger bending action), indicating that the gel strain sensor has excellent electrical signal stability. And its relative resistance change is positively correlated with the finger bending angle (tensile strain), which is consistent with the Figure 6 The results shown in (d) are consistent. Figure 6 As shown in (k), when monitoring the 30° bending of the finger, the response time and recovery time of the gel strain sensor do not exceed 200ms, which is limited by the back-end signal acquisition frequency (0.1s / time, 10Hz), but is sufficient to realize the recognition and monitoring of high-frequency movements of the human body.
[0102] In Test Example 1, it has been proved that the hydrogel provided by the present invention can maintain good flexibility, stretchability and quality stability under extreme environments of -30°C and 70°C. Furthermore, its conductivity change is tested in the temperature range of -30°C to 70°C. The test results are as follows: Figure 7As shown in (a), AgNPs can significantly improve the conductivity of the sample in a sub-zero temperature environment. The hydrogel sample containing AgNPs can still maintain good conductivity at -30°C; and as the temperature rises, the charge carriers increase and the sample resistance decreases, indicating that the hydrogel sample also has temperature responsiveness. Furthermore, the temperature responsiveness of hydrogel samples with different AgNPs contents is evaluated by the temperature coefficient of resistance (TCR), TCR = [(R-R0) / R0] / ΔT, where R is the instantaneous resistance at the test temperature, R0 is the initial resistance, and ΔT is the temperature difference. Figure 7 As shown in (b), (c), (d) and (e), the TCR of the hydrogel samples of Comparative Example 1, Example 1, Example 2 and Example 3 in the temperature range of -20°C to 25°C is -1.842%°C respectively. -1 (R 2 =0.987), -1.739%℃ -1 (R 2 =0.959), -1.772%℃ -1 (R 2 =0.986), -0.019%℃ -1 (R 2 =0.998), it can be found that as the content of AgNPs in the hydrogel sample increases, its TCR decreases, and the TCR value of the hydrogel sample of Example 3 suddenly decreases, which is only one percent of the hydrogel sample of Example 2. This is because a large number of AgNPs form a stable conductive path inside the hydrogel, and its relative resistance change is less affected by temperature changes. Therefore, hydrogel samples with different AgNPs contents can be selected according to the different needs of application scenarios.
[0103] Test Example 4
[0104] The mechanical properties, electrical conductivity and elastic modulus of the hydrogel sample can be adjusted by adjusting the content of AgNPs. AgNPs are also a safe and efficient antibacterial agent. Therefore, the high and low temperature resistant conductive antibacterial hydrogels prepared in Examples 1-3 and the PVA hydrogel prepared in Comparative Example 1 were tested for antibacterial properties. Escherichia coli [CMCC (B) 44102] was used as a representative of Gram-negative bacteria, and Staphylococcus aureus [CMCC (B) 26003] was used as a representative of Gram-positive bacteria, which were purchased from Nanjing Lezhen Biotechnology Co., Ltd. The antibacterial performance test was carried out by the inhibition zone method (inhibition rate PI) and the oscillation culture method (inhibition rate R), and the calculation method is as follows:
[0105] Inhibition rate PI = d i / d h *100%
[0106] where d iis the diameter of the inhibition zone, d h is the sample diameter (mm);
[0107] Antibacterial rate R = (BC) B * 100%
[0108] Among them, B is the colony count of the control group, and C is the colony count of the test group.
[0109] The inhibition zone method was used to preliminarily determine the antibacterial properties of the hydrogel samples. The test results are as follows: Figure 8 As shown in (a), position 1 corresponds to the hydrogel sample of Example 1, position 2 corresponds to the hydrogel sample of Example 1, position 3 corresponds to the hydrogel sample of Example 2, and position 4 corresponds to the hydrogel sample of Example 3. It can be seen that the hydrogel sample of Example 3 can show an obvious inhibition zone. The inhibition rate (PI) against E. coli and S. Aureus was calculated by measuring the diameter of the inhibition zone to be 389.59% and 419.97%, respectively. After 28 days, there was no obvious change in the inhibition zone. The antibacterial effect was very significant and long-lasting and stable. It is worth noting that after 7 days, a ring-shaped "silver film" appeared on the upper surface of the hydrogel sample of Example 3 and the surrounding culture medium surface. According to Fajans' rules, the unreduced Ag in the gel sample + The positively charged Ag in the hydrogel sample of Example 3 is mainly adsorbed around the AgNPs. + / AgNPs are attracted by the surrounding negatively charged E.coli and S.Aureus under the action of Coulomb attraction. AgNPs aggregate to form a donut-shaped "silver film" and show a long-lasting and significant antibacterial effect.
[0110] The oscillation culture method was used to quantitatively test the antibacterial rate (R) of the hydrogel samples. The test results are shown in Figure 8 As shown in (b), no colonies were detected in all the hydrogel samples containing AgNPs, so the colony count was recorded as "<1" for calculation of the antibacterial rate, and the antibacterial rates for E. coli and S. Aureus were ≥99.56% and ≥99.76%, respectively, with significant antibacterial effects. The hydrogel samples of Example 1 and Example 2, which did not show obvious inhibition zones, had an antibacterial rate of more than 99% against Gram-negative bacteria E. coli and Gram-positive bacteria S. Aureus, and therefore had safe and efficient antibacterial properties, and the inhibitory effect on S. Aureus was slightly higher than that on E. coli.
[0111] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a high and low temperature resistant conductive antibacterial hydrogel, characterized in that: The following steps are involved: (1) dissolving a high molecular alcohol polymer in a low freezing point mixed solution to obtain a pre-gel solution; (2) adding a silver salt solution to the pre-gel solution obtained in step (1) at 85° C. to 95° C. to react to obtain a hydrogel precursor solution; (3) The hydrogel precursor solution obtained in step (2) is subjected to freeze-thaw treatment to obtain the high and low temperature resistant conductive antibacterial hydrogel.
2. The preparation method according to claim 1, characterized in that: In step (1), the low freezing point mixed solution is a mixed solution of one or more polyols and water.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the low freezing point mixed solution to the high molecular alcohol polymer is 100:(5-20).
4. The preparation method according to claim 1, characterized in that: In step (1), the average molecular weight of the high molecular alcohol polymer is 20,000-150,000.
5. The preparation method according to claim 1, characterized in that: In step (1), a high molecular alcohol polymer is dissolved in a low freezing point mixed solution at 50°C to 95°C.
6. The preparation method according to claim 1, characterized in that: In step (2), the silver salt solution is selected from one or more of a silver ammonia solution, a silver nitrate solution, a silver oxalate solution, a silver chloride solution and a silver bromide solution.
7. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of the pre-gel solution to the silver ions in the silver salt solution is (30-70):(0.2-1.5).
8. The preparation method according to claim 1, characterized in that: In step (3), the freeze-thaw treatment conditions are: freezing at -25°C to -20°C, and thawing at 0°C to 70°C.
9. The high and low temperature resistant conductive antibacterial hydrogel prepared by the method according to any one of claims 1 to 8.
10. Use of the high and low temperature resistant conductive antibacterial hydrogel according to claim 9 in sensors and biological signal collection.
Citation Information
Patent Citations
Preparation method of nano-silver-loaded polyvinyl alcohol hydrogel
CN106009442A
Application of polyvinyl alcohol-nano silver composite material in Raman spectrum for detecting crystal violet
CN107525794A
Preparation method of silver nanowire / PBAT (poly(butyleneadipate-co-terephthalate)) nanometer fiber / polyvinyl alcohol composite conductive hydrogel
CN108794770A
Tough and anti-freezing ionic conductive hydrogel and preparation method thereof
CN116355257A